Can Yoga Overcome Criminality? The Impact of Yoga on Recidivism in Israeli Prisons - Kovalsky, Shaked (International journal of offender therapy and comparative criminology, 2020)
In recent years, yoga practices have been integrated into formal prison rehabilitation programs of the Israel Prison Service (IPS), as part of the informal education system, giving rise to innovative criminological theories such as positive criminology that emphasize the development of offenders’ strengths by facilitating rehabilitation and reintegration processes. The purpose of the present study was to examine the correlation between yoga practice and recidivism among released prisoners who participated in yoga programs during their incarceration in comparison with a matched control group of those who did not participate in yoga programs over a follow-up period of 5 years. To examine the effectiveness of the program, propensity score matching was used to compile the comparison group from among all convicted prisoners who were released from the Israeli prisons. Study results indicate that yoga may affect recidivism, supported by a finding of lower recidivism rates among released prisoners who had practiced yoga during their incarceration, compared with a matched control group. However, further study is needed including randomized controlled trials (RCTs). In light of these positive results, we recommend policy-makers consider expanding alternative practices such as yoga into prisons, in recognition of their contribution to the rehabilitation process through the development of personal and social strengths.